TEACHING ON THE FRONTLINES: VOICES OF FUTURE EDUCATORS IN KAMPUS MENGAJAR PROGRAM BATCH 7 - Rahmia, Nurul Syakinah; Syarif, Andi Rachmawati; Amin, Syarif (Universitas PGRI Semarang, 2025)
This study aims to explore the experiences of English Education pre-service teachers who participated in the Kampus Mengajar Batch 7 program. Data were collected through semi-structured interviews with seven participants using qualitative phenomenological methods. Then, thematic analysis was used to analyze the data. The results revealed six main themes: challenges in teaching and program implementation, stress and obstacles during the program, strategies to overcome obstacles, self-development as prospective educators, the relationship between theory and practice, and understanding the reality of education. Key challenges included lack of confidence in teaching, poor school facilities, weak internet connectivity, and limited support from schools. Nevertheless, participants developed strategies such as time management, communication, and teamwork to adapt to field conditions. The study concludes that despite the various obstacles, the Kampus Mengajar program provides valuable learning experiences that contribute to students' professional growth and understanding of the educational field in real contexts.